The MATH COMICS TO IMPROVE MATHEMATICAL COMMUNICATION SKILLS - Samara Alifa Jazuli; Syafmen, Wardi; Falani, Ilham (EMTEKA: Jurnal Pendidikan Matematika, 2024)
This research and development aims to determine the quality of mathematical comics using the PBL model in improving students' mathematical communication skills in terms of validity, practicality and effectiveness. The method used in this research is Research and Development using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The results obtained in this research were that the material validation percentage was 82.6% in the "very valid" category, the design validation percentage was 74.28% in the "valid" category, the teacher practicality percentage was 94%, classified as "very practical" , the percentage of students' practicality obtained was 85.26% in the "very practical" category, the percentage of effectiveness of students' responses was 83.04% in the "very effective" category and the N-gain calculation in increasing students' mathematical literacy skills was 74% with the "category" effective enough". So it is concluded that this research shows that mathematics comics using the PBL model in improving students' mathematical communication skills are suitable for use during the learning process because they meet the valid, practical and effective categories.